UTILIZATION OF CACAO FRUIT PEEL (Theobroma cacao) AS A BIOSORBENT OF Ni(II) IONS METAL - Malimongan M; Nursiah La Nafie; Paulina Taba (Hasanuddin University, 2015)
Nickel is one of the heavy metals which is very dangerous because it is carcinogenic and can cause a variety of acute and chronic diseases. Biosorption is one alternative method for the removal of heavy metals from the environment using a biomaterial called biosorbent. Biosorption of Ni(II) ion using cacao fruit peel (Theobroma cacao) with variation of contact time, pH and concentration has been investigated. The concentration of Ni(II) ion before and after adsorption was determined by Atomic Absorption Spectrophotometer (AAS). The result showed that cacao fruit peel (Theobroma cacao) was able to adsorb Ni(II) ion and the optimum biosorption occured at a contact time of 10 minutes and at a pH of 5. Langmuir and Freundlich isotherm models were used to study the adsorption isotherm. Biosorption of Ni(II) ion by cacao fruit peel (Theobroma cacao) fulfilled the Langmuir isotherm with a biosorption capacity of 0,21 mmol/g. The functional groups involved in the biosorption of Ni(II) ion by cacao fruit peel (Theobroma cacao) are –OH and N-H.